Structure-function relationships of type II restriction endonucleases - Uyar, Arzu. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Restriction endonucleases (REs) constitute an enzyme family, which can recognize and cleave specific foreign DNA sequences to protect prokaryotic cells. The vibrational dynamics of Type II REs are investigated by elastic network models, namely Gaussian Network Model (GNM) and Anisotropic Network Model (ANM), in order to analyze their structure-function relationships. Collective deformations of both apo REs and their specific complexes with DNA indicate scissor-like (ratchet-like) rotations and twisting-type motions in the slowest modes of dimeric and tetrameric REs. These motions can give insights about the sliding mechanism for target site location and the oscillation between closed and open states of REs, respectively. These modes are shown to be present in the non-specific complexes of EcoRV and BamHI, which further indicates their functional importance in terms of DNA recognition and sliding mechanism. Some important differences between cognate and non-cognate complexes of EcoRV and BamHI in terms of orientational cross-correlations are detected in functionally important two modes. Hot spot residues determined from high-frequency modes are clustered around the DNA binding region and at the DNA nodes, which indicates a possible communication pathway between cleavage sites.
Keywords: Restriction enzymes, DNA.; Endonucleases.